Faktor Internal dan Eksternal Pilihan Studi Lanjutan atau Dunia Kerja Siswa SMA Muhammadiyah Cirebon - Alif Ramdhani; Ira Namira; Olistriawan Olistriawan; Syahfira Syahfira; Tasini Tasini; Vany Dwi Putri; Anita Kusumaningrum (Universitas Nurul Jadid, 2026)
Post-secondary decision-making is an important phase in students’ career development because it directly influences their educational pathways, employment opportunities, and future socio-economic mobility. This study aims to analyze the tendency of twelfth-grade students at SMA Muhammadiyah Cirebon in choosing between pursuing higher education and directly entering the workforce, as well as to identify the internal and external factors influencing their decisions. This research employed a descriptive quantitative approach, using questionnaires and interviews as data collection techniques involving 60 students. The data were analyzed through descriptive statistics to identify preference patterns, percentage tendencies, and dominant factors underlying students’ choices. The findings indicate that most students tend to pursue higher education due to personal interests, future aspirations, academic self-efficacy, the desire to improve competence, long-term career prospects, and family support. Meanwhile, some students choose to enter the workforce immediately due to family economic conditions, the desire for financial independence, available job opportunities in their surroundings, and limited information about access to higher education. These findings suggest that post-secondary choices are shaped not only by individual aspirations but also by socio-economic realities and environmental support. Therefore, career guidance services in schools need to be strengthened to help students make realistic, well-directed decisions that align with their potential, interests, and individual circumstances.